2019
DOI: 10.1109/lcomm.2019.2912601
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Dropping Algorithm for Line-of-Sight Massive MIMO With Max-Min Power Control

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The reduction of the sum-rate due to the high correlation is considerable for LOS environments with max-min power control as reported in [5], [6] (max-min power control is used to provide uniformly good service for the users as reported in [3]). In addition, it is shown in [5,Fig. 2] that when there is only one pair of highly correlated users, the signal to noise ratio with max-min power control will drop significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of the sum-rate due to the high correlation is considerable for LOS environments with max-min power control as reported in [5], [6] (max-min power control is used to provide uniformly good service for the users as reported in [3]). In addition, it is shown in [5,Fig. 2] that when there is only one pair of highly correlated users, the signal to noise ratio with max-min power control will drop significantly.…”
Section: Introductionmentioning
confidence: 99%
“…2] that when there is only one pair of highly correlated users, the signal to noise ratio with max-min power control will drop significantly. To deal with highly correlated scenarios in LOS environments with max-min power control, [3], [5], [6] studied dropping algorithms. However, dropping users may not be desirable in the case of latency-sensitive communication.…”
Section: Introductionmentioning
confidence: 99%
“…which incorporates the small-scale fading effect. In [7] it is shown that how the sum-rate of a MU-MIMO system is being decreased as the correlation among two users increases, while linear precoders are applied. The normalized spatial correlation between two users can be computed by:…”
Section: Nlos Channel Model and Spatial Correlationmentioning
confidence: 99%
“…In this section, THP with two power allocation schemes is reviewed. The THP sum-rates of the two power allocation schemes are derived for a "correlated channel of size K" defined in [8,Definition 1]. In this type of channel, user K −1 and user K are the only correlated pair of users.…”
Section: System Model and Preliminariesmentioning
confidence: 99%
“…A similar criterion was used in [6], [7]. Instead of simulationbased thresholds as in [3], thresholds are derived in [8] for CB and ZF with max-min power control.…”
Section: Introductionmentioning
confidence: 99%